The vagaries and value of the army transport mule in the British army during the First World War1. Issue 248 (11th October 2016) - Varnava, Andrekos
Abstract: This article aims to write the army transport mule, which has previously been neglected in the equine historiography of the conflict, into the story of the First World War. It does not aim to tell the entire story of the role of mules in the war, as this deserves fuller investigation. Instead, it focuses on how various British sources depicted the army transport mule and how the actual involvement and treatment of these animals on the Salonica Front accorded with these perceptions.